Visualizing geometric algorithms over the Web - Baker, James E.; Cruz, Isabel F.; Liotta, Giuseppe; Tamassia, Roberto (Computational geometry : theory and applications, 1999)
The visual nature of geometry applications makes them a natural area where visualization can be an effective tool for demonstrating algorithms. In this paper we propose a new model, called Mocha, for interactive visualization of algorithms over the World Wide Web. Mocha is a distributed model with a client-server architecture that optimally partitions the software components of a typical algorithm execution and visualization system, and leverages the power of the Java language, which has become the standard for distributing interactive platform-independent applications across the Web. Mocha provides high levels of security, protects the algorithm code, places a light communication load on the Internet, and allows users with limited computing resources to access executions of computationally expensive algorithms. The user interface combines fast responsiveness with the powerful authoring capabilities of hypertext narratives. We describe the architecture of Mocha, show its advantages over previous methods, and present a prototype that can be accessed by any user with a Java-enabled Web browser. The Mocha prototype has been widely accessed over the Web, as demonstrated by the statistics that we have collected, and the Mocha model has been adopted by other research groups. Mocha is currently part of a broader system, called GeomNet, which performs distributed geometric computing over the Internet.